Pengaruh Gaya Mengajar Guru Tua dan Muda PAI Terhadap Sikap dan Motivasi Belajar Siswa di Kelas XI IPA MA Assalam Buaran Bantarkawung Brebes - Bagus priyo sembodo; Hanifuddin Hanifuddin (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the effect of teaching styles of old and young PAI teachers on students' attitudes and learning motivation in Class XI IPA MA Assalam Buaran Bantarkawung Brebes. This research uses a quantitative approach to research. The population in this study were students of class XI IPA MA assalam. The sample technique for class XI IPA is 30 students. Retrieval of data in this study is the method of documentation and questionnaires. The data analysis technique used percentage descriptive analysis, classical assumption test, and multiple linear regression analysis with the help of SPSS IBM 28. Based on the results of the study, it can be concluded as follows: 1) there is no effect on learning attitudes of PAI Old Teacher Teaching Styles obtained tcount of -2,397 < from ttable 2,052 and a sig value of 0.024. 2) there is an influence on the learning attitude of the young PAI teacher's teaching style, the tcount value is 3,321 > from the ttable 2.052 and a sig value of 0.003. 3) there is no effect on the learning attitude of the Old PAI Teacher's Teaching Style, obtained a tcount value of -2,666 < from ttable 2,052 and a sig value of 0.013 4) the results of the influence on the learning attitude of the Young PAI Teacher's Teaching Style obtained a tcount value of 4,129 > from ttable 2,052 and sig value < 0.001.